Record of human activities in the Pb isotopes signatures of coastal sediments from the Roman archaeological site of Cala Francese, Cape Corsica (France). (April 2017) - Fagel, Nathalie; Lechenault, Marine; Fontaine, François; Pleuger, Elisa; Otten, Joel; Allan, Mohammed; Ghilardi, Matthieu; Mattielli, Nadine; Goiran, Jean-Philippe
Abstract: The Mediterranean margins were characterized by intense maritime commercial exchanges since Antiquity. We conducted a lead isotope study of coastal sediments from Cala Francese, a Roman archaeological site at Cape Corsica (France) with the aim of evaluating the environmental contamination of lead over the historical period. The Pb content and isotope composition have been measured on the upper sections of three sedimentary columns. According to a radiocarbon chronological framework, the sampling interval covers the last ~ 3500 to 4000 years. Our results indicate that Pb enrichments in the Cala Francese sediments began during the Roman period and changes in the corresponding Pb isotope signatures are consistent with human perturbations of the local environment since the Roman period. Based on a literature compilation of the potential Pb mining districts, we discuss the sources of the Pb contamination. In addition to recording the signature of global atmospheric pollution in the upper samples, the Cala Francese site records a local contamination due to Roman occupation, as indicated by the occurrence of potsherds. The Miocene Pb mining districts from Cartagena and Mazaron in SE Spain are identified as the most probable sources of the local contamination, and are consistent with the archaeological information of the Roman trade routes. Highlights: Pb isotope composition of coastal sediments attests for a local contamination of the site of Cala Francese, Cape Corsica Cala Francese site records a Pb contamination due to Roman occupation Alpine ores from Southeastern Spain are identified as the probable source of contamination, in agreement with Roman trades. Pb isotope study confirms the archaeological importance of Cala Francese within the Mediterranean exchanges over Roman period